Online assessment in ELT: Teachers’ practices and challenges - Ermayati, Ermayati; Saefurrohman, Saefurrohman (Universitas Islam Sultan Agung, 2025)
This qualitative case study investigates the online formative assessment practices and the challenges faced by junior high school English teachers in Banyumas Regency. Utilizing observations, semi-structured interviews, and document analysis with five purposively selected teachers, the study explores the practical implementation of digital assessment tools in English Language Teaching (ELT) classrooms. Findings reveal that teachers actively utilize interactive platforms like Quizizz, Google Forms, and Wordwall, primarily for quick quizzes and immediate feedback, demonstrating a clear alignment with learning objectives. This approach significantly boosts student motivation and engagement, largely owing to the tools' interactive and gamified features. However, the path to seamless integration is marked by several key hurdles. Prominent challenges include limited student access to suitable devices and reliable internet connectivity, persistent technical issues with platforms and signals, students' initial unfamiliarity with online tools, and significant concerns over phone misuse and academic integrity. Additionally, teachers themselves reported perceived gaps in their experience and digital skills. These insights collectively emphasize the crucial need for enhanced technological infrastructure, tailored professional development for educators, and supportive policy frameworks to effectively realize the full potential of online formative assessment in ELT